2011
DOI: 10.1016/j.neurobiolaging.2009.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated tau 231, memory decline and medial temporal atrophy in normal elders

Abstract: Little is known whether cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease (AD) can predict both memory decline and associated longitudinal medial temporal lobe (MTL) gray matter (GM) reductions in cognitively healthy individuals. 57 normal elderly subjects received comprehensive evaluation at baseline and 2 years later. The baseline phosphorylated tau 231 (ptau 231 ), total tau, the amyloid beta (Aβ) Aβ42/Aβ40, t-tau/Aβ42 and p-tau 231 /Aβ42 ratios were examined as predictors of memory change and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 38 publications
7
29
0
Order By: Relevance
“…The evidence for the benefit of CSF biomarkers in AD research is highly compelling as many studies have shown the utility of the AD signature (low Aβ 42 together with high T-tau and P-tau) for AD diagnosis and have demonstrated its use as a predictor of disease progression [56,59,60,62,103,111,112]. Indeed, the high sensitivity/specificity of the AD signature could lead to its development as the “gold standard” in early/prodromal AD diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for the benefit of CSF biomarkers in AD research is highly compelling as many studies have shown the utility of the AD signature (low Aβ 42 together with high T-tau and P-tau) for AD diagnosis and have demonstrated its use as a predictor of disease progression [56,59,60,62,103,111,112]. Indeed, the high sensitivity/specificity of the AD signature could lead to its development as the “gold standard” in early/prodromal AD diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited data are available on combined CSF and imaging biomarkers in cognitively normal populations, and these offer inconsistent results. While some studies have found that decreased CSF Aβ42 is associated with cognitive decline among normal older adults [2730], others could not confirm these observations [31, 32]. Prior work by Palmqvist and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Pittsburgh Compound B (PiB) retention was found in thalami and striatum both by us (Mosconi et al ., 2010) and others (Klunk et al ., 2008; Koivunen et al ., 2008; Scholl et al ., 2009) in subjects at risk or with AD. Even though these amyloid deposits are not believed to be related to cell loss (Klunk et al ., 2008) and the relationships between amyloid burden and atrophy are less consistent than relationships between neurofibrally pathology and atrophy (Josephs et al ., 2008; Fagan et al ., 2009; Driscoll et al ., 2010; Glodzik et al ., 2010), a recent report demonstrated an association between PiB retention and gray matter atrophy on a region by region basis (Chetelat et al ., 2010). Since CSF Aβ42 correlates with PiB retention in subjects without dementia (Fagan et al ., 2006), we speculate that the observed correlations between CSF Aβ42/Aβ40 and GM may reflect a subtle regional atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…This, we speculate, corroborates the utility of tau to Aβ42 ratio concept. As in our previous work we used Aβ42/Aβ40 ratio instead of Aβ42 alone (Brys et al ., 2008; Glodzik et al ., 2010). In our experience ratio better reflects possible AD, since the concentration of Aβ42 is determined not only by ongoing pathology but also by the total CSF Aβ peptide concentration which is individually different (Wiltfang et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation